Traduction est un jeu d’oulipien ou sur le caractère ludique et oulipique de la traduction - Paliczka, Anna (Romanica Silesiana)
The article is a theoretical consideration on translation perceived as a game. The aforementioned game, whose constituents were brought up at the beginning of the article, bears features typical of the practice of writing texts during the Thursday meetings of the OuLiPo members. The author assumes that every literary text is a result of the game proposed by the writer. The translator faces the challenge posed by the original text, and by translating it into a different cultural and linguistic reality, he makes his next move in the game. During the analysis of his actions, it occurs that translation resembles writing texts under strict rules. The ludic character of translation is also confirmed in the article by selected translators, who share their experiences related to the art of translation. The translator, just like an Oulipian, draws from the richness of language and literature, creating new texts based on those which have already been created. A translation’s level of difficulty depends on the source text’s type and characteristic, its cultural origin, as well as the culture of the target text. These elements constitute a sort of constraints, determining the choices made by the translator, nonetheless giving him some freedom as well. Translations are similar to OuLiPo practices, relying on intellectual exercise and the joy of creation, the purpose of which is to ensure that there is a continuity and freshness in literature and to provide it with new tools and structures. Key words: Game, translation, Oulipian works.